Dietary Therapies in Pediatric Crohn’s Disease - Kamińska, Izabela; Pawłocik, Weronika; Pawlak, Weronika; Grabowska, Ewa; Szymańska, Julia; Wojtala, Laura; Rymarz, Anna; Kojder, Dominika; Piekarska, Małgorzata; Jedlina, Klaudia (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Crons’ disease is a chronic illness of the digestive system. Its etiology is multifactorial and one of the factors is nutrition. That is why the researchers are trying to labour the valuable types of dietary therapy, which could be used in treatment of pediatric CD. The purpose of our review is to point out the impact of dietary therapy on achieving remission in pediatric Crohn’s disease. Materials and methods: We have reviewed the literature from the PubMed database searching for clinical trials, meta analysis and randomized controlled trials from the past years. The keywords we agreed on offered us the most informative articles and made us hope for the further development of our article. Brief Description Of The State Of Knowledge: Steroid therapy is the principle of CD treatment, but it has a number of side effects that influence the quality of pediatric patients’ life. It has been shown that the use of dietary therapies (EEN, CDED+PEN, SCD) enables the achievement of clinical and biochemical remission, mucosal healing and regulation of dysbiosis. There are many hypotheses explaining this effect, probably the reason of this is the exclusion from the diet of food products that provoke inflammatory processes. Summary: Despite its effectiveness, dietary therapies require motivation and full commitment from patients in order to achieve results. That is why it is so important to conduct further research in this area so that the selected therapy is as acceptable and tolerated by the patient as possible. In addition, education of children and parents, psychological and dietary support are also crucial in the treatment process.